The ambassadors. Vol. 1 - Millar, Mark (Image Comics, 2023)
"Six people on the planet are about to get superpowers. Please choose carefully. The secret of superhumanity has been cracked and six civilians from different countries are about to have their lives changed forever. But who do you trust with Earth-shattering powers?" --